Multicriteria evaluation of discharge simulation in Dynamic Global Vegetation Models. Issue 15 (8th August 2015) - Yang, Hui; Piao, Shilong; Zeng, Zhenzhong; Ciais, Philippe; Yin, Yi; Friedlingstein, Pierre; Sitch, Stephen; Ahlström, Anders; Guimberteau, Matthieu; Huntingford, Chris; Levis, Sam; Levy, Peter E.; et al.
Abstract In this study, we assessed the performance of discharge simulations by coupling the runoff from seven Dynamic Global Vegetation Models (DGVMs; LPJ, ORCHIDEE, Sheffield‐DGVM, TRIFFID, LPJ‐GUESS, CLM4CN, and OCN) to one river routing model for 16 large river basins. The results show that the seasonal cycle of river discharge is generally modeled well in the low and middle latitudes but not in the high latitudes, where the peak discharge (due to snow and ice melting) is underestimated. For the annual mean discharge, the DGVMs chained with the routing model show an underestimation. Furthermore, the 30 year trend of discharge is also underestimated. For the interannual variability of discharge, a skill score based on overlapping of probability density functions (PDFs) suggests that most models correctly reproduce the observed variability (correlation coefficient higher than 0.5; i.e., models account for 50% of observed interannual variability) except for the Lena, Yenisei, Yukon, and the Congo river basins. In addition, we compared the simulated runoff from different simulations where models were forced with either fixed or varying land use. This suggests that both seasonal and annual mean runoff has been little affected by land use change but that the trend itself of runoff is sensitive to land use change. None of the models when considered individually show significantly better performances than any other and in all basins. This suggests that based on current modeling capability, a regional‐weighted average of multimodel ensemble projections might be appropriate to reduce the bias in future projection of global river discharge.